Penerapan Data Mining Dalam Menentukan Pola Penjualan Alat Tulis Kantor (Atk) Menggunakan Algoritma Apriori Pada Toko Novacom - Aldo Daniel Purba; Poningsih; Widodo Saputra; Dedy Kristianto Lumbantobing; Sumarno (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Office stationery is a necessity that is indispensable in the world of offices and education because it has usefulness in helping and lightening when doing daily tasks in various types of work and circles. This research place sells various kinds of office stationery such as pens, books, pencils and various other types of equipment. Many piles of data that are not used effectively are a problem for Novacom office stationery shop owners. Because of the pile of data, a settlement or pattern formation is needed in order to assist shop owners in determining sales patterns and provide recommendations to shop owners what items are most often purchased by consumers. The algorithm that will be used as an analysis process for office stationery sales is the a priori algorithm to show the results that have met the determination of the pattern of buying office stationery based on sales to consumers